(untitled) (EU and comparative law issues and challenges series (ECLIC), 2019)
Authors are researching development and analyzing first effects of cross-border investigative measures, following enactment of the European Investigation Order (EIO). The EIO extends number of investigative actions which can be requested from other countries, and simplifies the process of evidence transfer. The paper is discussing problems during development of the EIO, its’ reception in Croatian system and a case study of the first orders received in Croatian police in 2018 is performed. This instrument is not imposing common legislative standards, but introducing the principle of mutual recognition which is derived from other law fields. The main risk is that diversity of some investigative measures could lead to the inadmissibility of evidence in subsequent criminal procedure. Results are showing that there hadn’t been obstacles in police practice so far. Main issues on principle of mutual recognition, double criminality or admissibility of evidence were not manifested in case study, but research indicates areas of potential problems.